A systematic review on the comparison of FOLFIRI and FOLFOX based chemotherapies in the treatment of metastatic colorectal Cancer - Islam, Nurjahan (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.